Development of integrated teaching materials vibration, wave and sound with ethnoscience of bundengan for optimization of students' scientific literation. Issue 5 (June 2021) - Rusilowatil, A; Sundari,; Marwoto, P
Abstract: The purpose of this study is to develop natural science teaching materials that integrate ethnoscience Bundengan in the Vibration, Wave and Sound material for the Central Java region. The specific purposes are describe the characteristics of the teaching materials developed, test their validity, level of readability and effectiveness in increasing students' scientific literacy. This development research uses the Borg & Gall development model, starting with the needs analysis, the development of teaching materials, the validity test and the readability of the teaching materials that have been developed, as well as the effectiveness of teaching materials. Validation is carried out by experts in the field of study (lecturer) and practitioners (science teacher). The subject of the reading test of textbooks and effectiveness was junior high school students in Wonosobo Regency. Test the readability of the book using the overlap test (cloze test). Data analysis techniques using percentages, normalized gain, and t test. The validity of the teaching materials for Vibration, Waves and Sounds integrated with ethnoscience Bundengan are very valid both in content, presentation and language. This teaching material is also able to increase students' scientific literacy higher than other teaching materials.